Canalization of auxin flow by Aux/IAA-ARF-dependent feedback regulation of PIN polarity - Sauer, Michael (Cold Spring Harbor Laboratory Press, 2006)
Plant development is characterized by a profound ability to regenerate and form tissues with new axes of polarity. An unsolved question concerns how the position within a tissue and cues from neighboring cells are integrated to specify the polarity of individual cells. The canalization hypothesis proposes a feedback effect of the phytohormone auxin on the directionality of intercellular auxin flow as a means to polarize tissues. Here we identify a cellular and molecular mechanism for canalization. Local auxin application, wounding, or auxin accumulation during de novo organ formation lead to rearrangements in the subcellular polar localization of PIN auxin transport components. This auxin effect on PIN polarity is cell-specific, does not depend on PIN transcription, and involves the Aux/IAA-ARF (indole-3-acetic acid-auxin response factor) signaling pathway. Our data suggest that auxin acts as polarizing cue, which links individual cell polarity with tissue and organ polarity through control of PIN polar targeting. This feedback regulation provides a conceptual framework for polarization during multiple regenerative and patterning processes in plants.